Rational choice theory : resisting colonization - Archer, Margaret S. (Margaret Scotford); Tritter, Jonathan Q., 1965- (Critical realism--interventions., 2001)
This fascinating title focuses on the four assumptions which are the bedrock of rational choice; rationality, individualism, process and aggregation and draws on a wide range of social issues such as race, marriage, and education.